A Sustainable Sugarcane Bagasse Biochar–Bentonite Composite for Peroxide Value Reduction in Used Cooking Oil - Wijayanti, Avissa Auryn; Yuniarto, Adhi; Nurhayati, Indah; Rochman, Sagita (Tecno Scientifica Publishing, 2025)
Used cooking oil underwent thermal and oxidative degradation due to repeated heating, resulting in increased peroxide levels and producing rancid odors, discoloration, and potential toxicity. In this study, the initial peroxide value of the used cooking oil was 56.42 meq O₂/kg, indicating significant oxidative degradation. The study evaluated the ability of activated sugarcane bagasse-bentonite (ASBB) and non-activated (SBB) composites to reduce peroxide values. Characterization was performed using SEM-EDX and FTIR, while adsorption efficiency was tested by varying the adsorbent dose (2–10 g) and treatment time (0–180 minutes). Peroxide reduction was analyzed using iodometric titration. The results showed that ASBB was more effective, with 10 g of ASBB and 180 minutes of treatment reducing the peroxide value by up to 82.3–84.5%.